An Alternative Dermal Template for Reconstruction of Complex Upper Extremity Wounds. Issue 7 (July 2021) - Wu-Fienberg, Yuewei; Wu, Shannon S.; Gatherwright, James; Chepla, Kyle J.
Abstract : Summary: The management of upper extremity soft-tissue defects with full-thickness skin loss and denuded tendon and/or bone traditionally requires vascularized tissue reconstruction. Herein, we present patient outcomes utilizing Novosorb Bio-degradable Temporizing Matrix (PolyNovo, Wilmington, Del.), a novel bilaminar dermal regenerative template, followed by skin grafting, for reconstruction of complex upper extremity injuries with exposed tendon and/or bone. We retrospectively reviewed all patients treated at our Level I trauma center with upper extremity trauma and exposed tendon and/or bone who had application of Novosorb Bio-degradable Temporizing Matrix over a 1-year period. At the time of surgery, all nonviable tissue was debrided, and the product was applied according to the manufacturer's instructions. If required, split thickness skin grafting was performed once neodermis appeared perfused, or after the sealing layer delaminated spontaneously. Six patients (four men, two women) with an average age of 49.8 (35–60) years were included in the study. Average defect size measured 97 cm 2 (10–440). Average time to complete healing was 45 days (27–57). Three patients reepithelialized spontaneously and did not require grafting; average defect size in these patients was 26 cm 2 (10–42). There were no infections and no loss of the dermal matrix or skin graft, when performed. All patients healed without complication after grafting and did not require further surgical treatment. Therefore, we contend that Novosorb BTM is a dermal regenerative template that shows potential as an alternative option to flap reconstruction in select patients after upper extremity trauma and soft-tissue defects with exposed tendon and/or bone. Further studies will be required to refine indications and evaluate outcomes.